2022
DOI: 10.1261/rna.079196.122
|View full text |Cite
|
Sign up to set email alerts
|

Biological solution conditions and flanking sequence modulate LLPS of RNA G-quadruplex structures

Abstract: Guanine-rich regions of DNA or RNA can form structures with two or more consecutive G-quartets called G-quadruplexes (GQ). Recent studies reveal the potential for these structures to aggregate in vitro. Here we report effects of in vivo concentrations of additives—amino acids, nucleotides, and crowding agents—on the structure and solution behavior of RNAs containing GQ-forming sequences. We found that cytosine nucleotides destabilize a model GQ structure at biological salt concentrations, while free amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…A similar destabilizing effect on RNA Gquadruplex structures has been reported specifically for cytidine nucleotides. 60 Interestingly, in the case of G-quadruplex structures, other nucleotides (A and U) had a smaller destabilizing effect, suggesting that G-quadruplexes are destabilized by favorable base pairing interactions between cytidine nucleotides in solution and Gs in the unfolded state of the RNA. The NTPCM is comprised mostly of ATP, UTP, and dTTP (22.5 mM total versus 4.9 mM GTP).…”
Section: ■ Discussionmentioning
confidence: 99%
“…A similar destabilizing effect on RNA Gquadruplex structures has been reported specifically for cytidine nucleotides. 60 Interestingly, in the case of G-quadruplex structures, other nucleotides (A and U) had a smaller destabilizing effect, suggesting that G-quadruplexes are destabilized by favorable base pairing interactions between cytidine nucleotides in solution and Gs in the unfolded state of the RNA. The NTPCM is comprised mostly of ATP, UTP, and dTTP (22.5 mM total versus 4.9 mM GTP).…”
Section: ■ Discussionmentioning
confidence: 99%
“…Studies on G4s have not yet been carried out purely in an intracellular setting due to the complexity of the intracellular environment. However, some research on G4s under physiological conditions has been conducted in environments that simulate molecular crowding. As a molecular crowding reagent for simulating the intracellular environment, it is required to increase the rejection volume, alter the water activity, and meet the requirement of not interacting directly with nucleic acids and the ligand. To achieve a purposeful study on the conformation of G4s and ligands, many reagents are used to simulate the molecularly crowded environment, such as poly­(ethylene glycol) (PEG), acetonitrile, glycerol, dextran, glucose, and dimethyl sulfoxide (DMSO), etc. , PEG with different molecular weights (PEG 200, PEG 400, PEG 2000, and PEG 8000) is commonly adopted to mimic the crowded cellular environment because it is water-soluble, is chemically inert, and does not interact efficiently with biological macromolecules.…”
Section: Reagents Simulating the Molecularly Crowded Environment In C...mentioning
confidence: 99%
“…However, some research on G4s under physiological conditions has been conducted in environments that simulate molecular crowding. 34 36 As a molecular crowding reagent for simulating the intracellular environment, it is required to increase the rejection volume, alter the water activity, and meet the requirement of not interacting directly with nucleic acids and the ligand. To achieve a purposeful study on the conformation of G4s and ligands, many reagents are used to simulate the molecularly crowded environment, such as poly(ethylene glycol) (PEG), acetonitrile, glycerol, dextran, glucose, and dimethyl sulfoxide (DMSO), etc.…”
Section: Reagents Simulating the Molecularly Crowded Environment In C...mentioning
confidence: 99%
“…Despite the existence of such flanking sequences, few studies have assessed how ribozymes are regulated in their native context. Interactions with flanking sequence can disrupt folding of the ribozyme and impair its function by favoring an alternative conformation. Alternatively, the flanking sequence may not interact with the ribozyme, allowing it to assume its active state and self-cleave.…”
mentioning
confidence: 99%
“…Indeed, interaction with flanking sequence is a universal mechanism that regulates functional RNAs beyond ribozymes. , For example, we reported that flanking sequence assists folding of an RNA thermometer in Bradyhizobium japonicum , by forming three upstream hairpins that do not interact with the thermometer . In another example, we found that the size and morphology of phase-separated droplets containing G-quadruplexes, a structural motif composed of layered G-quartets, are dictated by the sequences flanking the G-quadruplex . In both large and small ribozymes, regulation by the flanking sequence has also been observed.…”
mentioning
confidence: 99%